The Demand for Labor Market Structure: An Economic Approach - Hendricks, Wallace E.; Kahn, Lawrence M. (Journal of Labor Economics, 1984)
This paper formulates and estimates a model for the determination of employer and union demand for multiemployer (vs. single employer) bargaining units. Utility-maximizing, risk-averse firms and unions are both assumed to weigh the impact of each type of bargaining unit on the expected level and variability of profits and wages, respectively. The model is tested on a 1975 sample of 3,486 individual collective bargaining agreements. Because either party can generally leave a multiemployer unit without the other party's consent, a partially observed bivariate probit model is used to estimate demand for structure. It is found that the forgone profits due to a multiemployer unit (relative to a single-firm unit) lower firm demands for this type of unit, while forgone wages in a multiemployer unit (relative to a single-firm unit) lower union demand for this type of unit.